Economic Sanctions as a Means of Influencing International Order as Seen in the Example of the Construction of the Nord Stream 2 Gas Pipeline - Bartosz PACHOLSKI (Communications of International Proceedings, 2020)
Sanctions in international law are a significant lever that serves to enforce rules of procedure which the international community perceives as desirable. They involve ensuring efficiency of application of international legal norms, as well as securing interests of actors operating under this order. In the reality of a global economy, particular significance is attributed to economic sanctions. Those who support their efficiency point to the key role of economic impact as a non-military measure, whereas opponents doubt their efficiency as an independent repressive measure and notice burdens associated with the application of economic measures for the authority that introduces them. The US defence budget act (National Defense Authorisation Act, NDAA) for 2020 adopted at the end of 2019 introduced economic sanctions against operators involved in the construction of the Nord Stream 2 gas pipeline whose second string is to connect directly the Russian Federation with the Federal Republic of Germany. The sanctions affected stakeholders involved in the construction of the pipeline who provided highly-specialised technology necessary to lay gas pipes at the bottom of the Baltic Sea, thus making the company Allseas withdraw from the project, and in consequence halted the work. The aim of this paper is to analyse the motifs, principles of introduction and effects of application of economic sanctions by the USA with regard to construction of the Nord Stream 2 pipeline. This purpose was implemented be means of the analytical method. The result of the study includes an assessment of the impact of measures applied by the USA on the international economic order and of compliance of decisions that were taken with international law.
Keywords: economic sanctions; international economic law; international relations; Nord Stream 2